2018
DOI: 10.1016/j.freeradbiomed.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Promastigote parasites cultured from the lesions of patients with mucosal leishmaniasis are more resistant to oxidative stress than promastigotes from a cutaneous lesion

Abstract: Human leishmaniasis caused by Leishmania (Viannia) braziliensis can be presented as localized cutaneous leishmaniasis (LCL) or mucosal leishmaniasis (ML). Macrophages kill parasites using nitric oxide (NO) and reactive oxygen species (ROS). The aim of this study was to evaluate the ability of parasites obtained from patients with LCL or ML to produce and resist NO or ROS. Promastigotes and amastigotes from LCL or ML isolates produced similar amounts of NO in culture. Promastigotes from ML isolates were more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Ávila et al showed that L. (V.) braziliensis promastigotes and amastigotes isolated from CL and ML patients produced similar amounts of NO in culture. However, promastigotes from ML isolates were found to be more resistant to NO and H 2 O 2 than CL parasites (Avila et al, 2018). Our results document that infection with DL isolates induces higher respiratory burst in monocytes from DL, CL and HS compared to isolates from CL, yet the observed enhancement in oxidative burst did not inhibit parasite multiplication, which suggests that DL isolates are less susceptible to monocyte killing than CL.…”
Section: A B D Cmentioning
confidence: 56%
“…Ávila et al showed that L. (V.) braziliensis promastigotes and amastigotes isolated from CL and ML patients produced similar amounts of NO in culture. However, promastigotes from ML isolates were found to be more resistant to NO and H 2 O 2 than CL parasites (Avila et al, 2018). Our results document that infection with DL isolates induces higher respiratory burst in monocytes from DL, CL and HS compared to isolates from CL, yet the observed enhancement in oxidative burst did not inhibit parasite multiplication, which suggests that DL isolates are less susceptible to monocyte killing than CL.…”
Section: A B D Cmentioning
confidence: 56%
“…Ávila et al showed that L. braziliensis promastigotes and amastigotes isolated from CL and ML patients produced similar amounts of NO in culture. However, promastigotes from ML isolates were found to be more resistant to NO and H 2 O 2 than CL parasites 42 . Our results document that infection with DL isolates induces higher respiratory burst in monocytes from both DL and CL patients compared to isolates from CL, yet the observed enhancement in oxidative burst did not inhibit parasite multiplication, which suggests that DL isolates are less susceptible to monocyte killing than CL.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, L. naiffi , which generally causes a benign and autoresolutive infection in humans, showed the lowest infection index and the highest NO production (Campos et al, 2008). In another study, promastigotes isolated from patients with mucosal leishmaniasis express more thiol-specific antioxidant protein, and were more resistant to nitric oxide and H 2 O 2 than strains obtained from localized cutaneous leishmaniasis (Ávila et al, 2018). Leishmania amazonensis , which is capable of inducing severe diffuse cutaneous form cursing with high parasite load and inactivation of macrophages, also developed strategies to escape from oxidative effects from phagocytes.…”
Section: How Parasite Promotes Survival In a Non-friendly Environment?mentioning
confidence: 99%
“…Two natural events proving the persistence of parasite are represented by 1- mucosal lesions produced years after primary cutaneous lesions (Leite et al, 2012; Ávila et al, 2018), and 2- the Post-Kal-azar dermal leishmaniasis (PKDL) after VL recovering (Ganguly et al, 2010; Singh et al, 2012; Zijlstra, 2016). In both cases, the same Leishmania species is able to produce, after healing, a different clinical form from primary manifestations.…”
Section: Leishmaniasis: a Brief Introductionmentioning
confidence: 99%